Association between osteoarthritis and dyslipidaemia: a systematic literature review and meta-analysis. Issue 2 (29th August 2017) - Baudart, Pauline; Louati, Karine; Marcelli, Christian; Berenbaum, Francis; Sellam, Jérémie
Abstract : Objectives: We aimed to investigate the prevalence of dyslipidemia in patients with osteoarthritis (OA) and whether OA and dyslipidemia are associated. Methods: We performed a systematic literature review and a meta-analysis, including cross-sectional, cohort and case–control studies, to assess the number of patients with OA and/or dyslipidemia. We calculated the mean (±SD) prevalence of dyslipidemia in patients with and without OA and the risk of dyslipidemia (OR, 95% CI) among patients with OA. Results: From 605 articles screened, 48 were included in the analysis (describing 29 cross-sectional, 10 cohort and 9 case–control studies). The mean prevalence of dyslipidemia was 30.2%±0.6% among 14 843 patients with OA and 8.0%±0.1% among 196 168 without OA. The risk of dyslipidemia was greater with than without OA overall (OR 1.98, 95% CI 1.43 to 2.75, p < 0.0001) and with knee OA (OR 2.27, 1.33 to 3.89, p = 0.003) and hand OA (OR 2.12, 1.46 to 3.07), p < 0.0001). Conclusion: The risk of dyslipidemia was twofold greater with than without OA, so lipid disturbances could be a risk factor for OA. Such a result supports the individualisation of the metabolic syndrome-associated OA phenotype.